Pendampingan Penulisan Artikel Dalam Meningkatkan Kemampuan Menulis Bagi Pembina di Dinas Sosial Yogyakarta - Zahrotus Saidah; Syahrizal Joe Muharam; Marshinta Indah Sari; Sintia Sebta Dwi Putri; Az Zahra Syamya Nabila; Ahmadan Q Alnizam (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
This mentoring aims to teach systematic, neutral, and logical writing techniques and present facts in detail to improve the writing and photography skills of the Yogyakarta Social Service Advisors. However, they often face challenges in detailed writing, using appropriate diction, and taking relevant photos. Therefore, intensive mentoring is needed to enhance the facilitators' writing and photography skills. This mentoring aims to teach systematic, neutral, and logical writing techniques and the ability to present facts in detail. Additionally, photography assistance focuses on lighting techniques, image composition, and selecting the right moments. This mentoring program consists of three stages: preparation (observation, problem identification, and solution discussion with partners), implementation (writing and photography mentoring for three days using interactive and practical methods), and evaluation (measuring the effectiveness of the mentoring and identifying areas for improvement). The results of the mentoring showed an improvement in the facilitators' writing and photography skills, as evidenced by the number of articles published on the Social Service website. Despite challenges such as conflicting schedules and limited technology, the participants' enthusiasm helped overcome these obstacles. This mentoring has positively impacted the facilitators' ability to present informative and heartfelt information to the public, providing education to a broader audience.